STRATEGI POLITIK PARTAI GOLONGAN KARYA (GOLKAR) DALAM UPAYA PEMENANGAN CALON LEGISLATIF PEREMPUAN PADA PEMILU 2019 KOTA PEKANBARU - Efendi, Resty Ardila; ', Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Under Act No. 7 of 2017 on Political Parties and Law No. 10 of 2008 on General Elections, which stipulates that women must have at least 30% representation in legislative elections and in the management of political parties, the problem in this study is the political strategy used by the Golkar party in the attempt to win the female legislative candidate in the 2019 elections in Pekanbaru City. The aim of this research is to find out the political strategies used by the Golkar Party in the effort to win female legislature candidates in the 2019 elections in Pukanbaru. This study uses Peter Schorder's Theory of Political Strategy, which is divided into three categories: offensive strategy and defence strategy. Defence Strategy is a typical strategy for a government majority. A mixture of defensive and offensive strategies that implement defensive strategic action against the opposition party as well as offensive action against its coalition. The method used in research is qualitative-descriptive. The data sources used are primary data and secondary data, with the data collection interview selecting seven people as samples. The results of the research show that many of the empowerment strategies carried out by women, ranging from the goal to the way it is implemented, represent this woman's voice and make many great efforts in its recruitment by implementing the strategies that the political party carries out in this fulfilment. Such strategies are offensive strategies, defensive strategies, and mixed strategies. Keywords: Golkar Party, Female Legislative Candidate, Strategy